Savings and Economic Growth in Botswana: An Analysis Using Bounds Testing Approach to Cointegration - Amusa, Kafayat (Journal of Economics and Behavioral Studies, 2013)
Economic growth boosted by high domestic savings has been advocated for by numerous economists throughout the years. For a country like Botswana where the savings- GDP ratio is relatively high, it becomes important to determine whether savings is indeed important for the economy. This paper reexamines the savings-growth debate for the Botswana economy by applying the Bounds testing approach to cointegration analysis to establish the relationship between domestic savings and economic growth in Botswana. The results indicate that domestic savings is significantly positively related to growth in Botswana. The study recommends the need for development of financial instruments to encourage domestic savings.